EVALUASI PROGRAM PENYEDIAAN RUANG TERBUKA HIJAU WILAYAH DKI JAKARTA - Riyawati Ika Dewi; Ahmansya; Diana Vivanti Sigit (Program Studi Manajemen Lingkungan, 2020)
The reality, must be faced by DKI Jakarta as the National Capital of Indonesia is population. The estimation data from the Jakarta Central Statistics Agency (BPS) in 2025, will be 11,034,000 people. This population is quite dense resulting in increased utilization of Natural Resources, and declining the Jakarta Environmental Quality Index (IKLH). The 2016 IKLH is 38.69 and 2017 is 35.78 and this is the lowest IKLH among 33 Indonesian Provinces. The Provision Green Open Space Program is one of the methods used by the DKI Jakarta Government to maintain the environmental quality of DKI Jakarta. For 2017 and 2018 did not reach the target for this program so it needs to be evaluated for the program that has been carried out in order to obtain in-depth findings. This research uses the evaluation method as Context, Input, Process Product (CIPP). Result: For the Context and Input components are in accordance with the expectations set while the Process and Product components do not meet the expectations set. Conclusion: Success of the program can be achieved if using innovative and creative ways and program evaluation must be done thoroughly by involving various supporting parties to find out the obstacles of program implementation